Characteristics of habitual posture in female wrestlers from the Polish National Team - Mrozkowiak, M.; Sokolowski, M.; Kaiser, A. (Medicina dello Sport, 2012)
Aim. The present study addresses the problem of the effect of the type of sport on body posture. This problem was analysed with an example of female wrestlers from a Polish national team. The aims of the study were: 1) to carry out diagnosis of habitual posture in female wrestlers; 2) to identify a type and degree of effect of specific wrestling training on body posture in female wrestlers; 3) to analyze the frequency of non-normative levels of parameters which describe body posture in female wrestlers, in a spatial manner, compared to girls who do not practise competitive sports. Methods. The study encompassed the period of February 2011 and was carried out among 30 members of the Polish National Wrestling Team (mean ± SD, age: 16,8 ± 1,21 years; body height: 163±5.77 cm; body mass: 54.1±9.28 kg). The method involved 29 measurements which described pelvis and physiological spinal curvatures in sagittal, frontal and transverse planes. A stand for computer-aided assessment of body posture (Posturometer M) was used in order to assess the level of the selected parameters which describe the pelvis-spine system. The most essential point in this method is that the measurements of all actual values of spatial situation of individual body sections are taken at the same time. The final results obtained from statistical methods specify minimal, maximal and mean values, standard deviation, correlation and multiple regression. The following results were compared with the measurements carried out among the population of girls who do not practise competitive sports. Results. A typical habitual posture of female wrestlers is characterised by a considerably elongated vertebral column in the section from C1 to S1, shallow depth of thoracic kyphosis and lumbar lordosis, significant asymmetry of pelvis, shoulders and scapulas, considerable reduction in the depth of spinal curvatures; the trunk is upright and the pelvis is usually twisted to the left. A higher frequency of disorders in static posture is observed in the area of partial angles in physiological curvatures and linear parameters of lumbar lordosis and thoracic kyphosis, asymmetry of shoulders, scapulae and pelvis. Conclusion. In consideration of systematic increase in the intensity and volume or training process, the necessity arises to perform more and more specialised diagnostics of health status and postural parameters during medical check-ups for competitive athletes. The essential importance for the process of elite wrestling training is from general conditioning exercises aimed at improving exercise capacity, health status and developing individual systems, organs and the body as a whole.